Methods to estimate the number of surface nucleation sites on glass particles - Ferreira, Eduardo B. [UNESP]; Nascimento, Marcio L. F.; Stoppa, Hugo; Zanotto, Edgar D. (My University, 2008)
Based on the Johnson-Mehl-Avrami-Kolmogorov (JMAK) theory, we propose two new models to describe the crystallisation kinetics of glass particles and use them to determine the density of nucleation sites, Ns, on glass powders. We tested these models with sintered compacts of diopside glass particles using sinter-crystallisation treatments at 825°C (T g∼727°C), that covered from null to almost 100% crystallised volume fraction. We measured and compared the evolution of the crystallised volume fractions by optical microscopy and x-ray diffraction. Then we fit our expressions to experimental data using Ns and R (the average particle radius) as adjustable parameters. For comparison, we also fit to our data existing expressions that describe the crystallised volume fraction in glass powders. We demonstrate that all the methods allow one to estimate Ns with reasonable accuracy. For our ground and water washed diopside glass powder, Ns is between 1010-1011 sites.m -2. The reasonable agreement between experimental and adjusted R confirms the consistency of all five models tested. However, one of our equations does not require taking into account the change of crystallisation mode from 3-dimensional to 1-dimensional, and this is advantageous.